Formulation and evaluation of colon specific microbial degradable matrix tablet using sterculia gum as carrier - Gouda, M Mallikarjuna; Shabaraya, A Ramakrishna; Kumar, S M Shanta (International Current Pharmaceutical Journal, 2012)
Current study is to develop the colon targeted matrix tablet using the natural polysaccharide sterculia gum as carrier and model drug ciprofloxacin HCl. The matrix tablets were prepared by wet granulation technology using the various proportions of sterculia gum with carbopol 934 P, sterculia gum and ethyl cellulose polymer blends. Granules of all formulations were evaluated for rheological, post compressional properties and in vitro dissolution study in different pH buffers of pH 1.2 , pH 7.4 , pH 6.8 (saline phosphate buffer) without and with 4% rat cecal content in order to mimic GIT condition . Formulation SGC2 to SGC4 and SGE7 to SGE9 has released 13.6% to 38.9% in the initial 5h and released more amount of drug in stomach and small intestine than colon. Formulation SGC5 containing 45% of sterculia gum and 25% carbopol 934 p and Formulation SGE10 containing 45% of sterculia gum and 25% ethyl cellulose has released minimum 10.91 % to 13.04 % in the initial 5h and sustained the drug release up to 24 h and at the end of study released 75% to 79.99%. Formulations with 4% rat cecal content at the end of 24 h study drug released is 90.44% to 95.33% indicating higher amount of drug release is due to enzymatic break down of sterculia gum in the matrix tablet. Hence the above results conclude that the formulation SGC5 and SGE10 are potential in targeting the drug to colon to treat irritable bowel disease. DOI: http://dx.doi.org/10.3329/icpj.v1i11.12064 International Current Pharmaceutical Journal 2012, 1(11): 376-383